THE POSITION OF SUPREME COURT REGULATION NUMBER 4 YEAR 2014 IN THE IMPLEMENTATION OF DIVERSION BY THE PUBLIC PROSECUTOR BASED ON THE REGULATION OF LAW - SATRIANI AS, ANDI; MAYASARI MUIN, AUDYNA; INDRAWATI, DARA (Sekolah Tinggi Ilmu Hukum Awang Long, 2020)
The judge continued to carry out diversions against a child who had committed a criminal offense, one of the articles of which was punishable by a sentence of under seven years. For the prosecutors themselves, there is no such rule, but in practice, in practice, many prosecutors carry out Supreme Court Regulations No. 4 Year 2014, in the sense that prosecutors continue to diversify children who commit crimes with a sentence of more than 7 years as long as the prosecutors overlay the charges. 7 years and under, and the average diversion is successful. This paper aims to analyze the position of Supreme Court Regulations Number 4 Year 2014 in the implementation of diversion by the public prosecutor based on the laws and regulations. The type of research used is social legal research. The data used are primary data (obtained directly from respondents and resource persons, namely the Luwu Office Attorney using interview techniques) and secondary data (various references or scientific papers in the field of law in the form of legal books and research documents related to previous data and statutory regulations. invitation). All data collected were analyzed qualitatively. The results show that the position of the Supreme Court Regulation Number 4 Year 2014 in the implementation of diversion by the public prosecutor is a rule that regulates the procedures for solving a problem in order to smooth the judiciary, in this case the implementation of diversion, given that there is a legal vacuum regarding the procedures for implementing diversion after the formation of the Law Number 11 Year 2012 concerning SPPA, where in the Law it is ordered that the Government Regulation regarding the implementation of diversion be made no later than 1 year from the enactment of the SPPA Law, but in reality the Government Regulation in question was promulgated outside of the stipulated time, so there is a vacancy law in the implementation of the SPPA Law. The Supreme Court which is given the authority by law to make complementary rules to fill the legal gaps or gaps has appropriately exercised its authority through the formation of the said Supreme Court Regulation.